ASUHAN KEBIDANAN PADA IBU F DENGAN PENERAPAN TERAPI MUROTTAL AL-QURAN UNTUK PENURUNAN NYERI PERSALINAN DAN KECEMASAN PADA IBU BERSALIN - Surya, Surya; Julianti, Rina; Asmanidar, Asmanidar; Norisa, Nanda (SINERGI : Jurnal Riset Ilmiah, 2025)
Introduction: Maternal mortality (MMR) has fallen by around 34% worldwide. An estimated 287,000 women lost their lives from mostly preventable causes related to pregnancy and childbirth in 2020, around 800 women every day or equivalent to 223 deaths per 100,000 Live Births (LBR). The Southeast Asia region maintained the fastest rate of reduction during the MDG era and the first five years of the SDG era, reducing the risk of maternal mortality from 372 deaths per 100,000 LBR in 2000 to 117 deaths per 100,000 LBR in 2020. Objective: The study provided midwifery care to Mrs. F to determine whether murottal Al-Quran had an effect on reducing maternal anxiety during childbirth. Research method: The design of this care was in the form of a case study with a qualitative approach. The subject of this case study was mother F, 24 years old, G2P1A0, at 40 weeks of pregnancy with anxiety during labor in West Aceh district. This study was conducted on February 2-2, 2025. Results: The results of the study showed that after being given care in the form of sounding and encouraging mothers to listen to murottal al-Quran during the labor process Conclusion: Midwifery care listening to murottal al-Quran has been proven to reduce anxiety in mothers in labor, murottal al-Quran can reduce anxiety in mothers in labor.